2013
DOI: 10.1111/jph.12198
|View full text |Cite
|
Sign up to set email alerts
|

Biocontrol of Late Blight Disease (Phytophthora capsici) of Pepper and the Plant Growth Promotion byPaenibacillus ehimensisKWN38

Abstract: For field application of a bacterial strain used to control Phythophthora capsici, we will need a biologically and economically efficient carrier medium. The known antagonist Paenibacillus ehimensis KWN38 was grown in a grass medium where it showed high antifungal and lytic enzyme activities. To demonstrate the potential of P. ehimensis KWN38 for biocontrol of late blight disease in pepper, pot trials were conducted by treating the 1-month-old plants with water (W), a selected grass medium (G3), G plus P. ehim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
12
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 43 publications
3
12
0
1
Order By: Relevance
“…These results agree with conclusion of Naing et al. (), who reported that soil enzyme activities were increased following inoculation of P. ehimensis KWN 38 and alleviated root death caused by infection with P. capsici zoopores.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…These results agree with conclusion of Naing et al. (), who reported that soil enzyme activities were increased following inoculation of P. ehimensis KWN 38 and alleviated root death caused by infection with P. capsici zoopores.…”
Section: Discussionsupporting
confidence: 93%
“…Soil enzyme activities in rhizosphere soils of diseased plants were increased compared to healthy plants in the presence of ASD strain in the present study. These results agree with conclusion of Naing et al (2014), who reported that soil enzyme activities were increased following inoculation of P. ehimensis KWN 38 and alleviated root death caused by infection with P. capsici zoopores.…”
Section: Discussionsupporting
confidence: 93%
“…(Virgen-Calleros et al 1997;Khabbaz et al 2015), Glomus intraradices (Zheng et al 2005), Aspergillus sp. (Kim et al 2009;Naing et al 2014). (Kim et al 2009;Naing et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In rice, the blast fungus Magnaporthe oryzae is considered to be the most important cause of disease (Ou 1985). Similarly, Pseudomonas fluorescens isolates have been found to control pre-emergence damping-off disease (Nielsen et al 1998), whereas inoculation of the roots of pepper plants with Paenibacillus ehimensis KWN38 increases plant growth and may control Phytophthora capsici infection (Naing et al 2014). One of the most promising approaches for an effective biological control strategy is the use of microbes for plant disease management.…”
Section: Introductionmentioning
confidence: 99%